2022
DOI: 10.1155/2022/3886710
|View full text |Cite
|
Sign up to set email alerts
|

The Amelioration of Detrimental Biochemical Anomalies by Supplementing B, C, and E Vitamins in Subjects with Type 2 Diabetes Mellitus May Reduce the Rate of Development of Diabetic Retinopathy

Abstract: Excessive intracellular glucose in insulin-independent tissues including nerve, nephron, lens, and retina invites mishandling of metabolism of glucose resulting in a background of increased oxidative stress, advanced glycation end products (AGE) formation, lipid peroxidation, and failure of antioxidant defense systems in type 2 diabetes mellitus (T2DM). All these detrimental biochemical anomalies ultimately attack biological membranes and especially capillary beds of the retina, resulting in the breakdown of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In this study, Pramanik et al followed 185 patients with T2DM who received vitamin B, vitamin C, and vitamin E together with antidiabetic medication and 175 patients with T2DM who were treated with only antihyperglycemic drugs for five years. The group with vitamin supplementation had a slower rate of the development of diabetic retinopathy and reduced ROS markers [ 12 ]. It is concluded that vitamin supplementation decreases the development of diabetic microvascular complications via their antioxidant properties.…”
mentioning
confidence: 99%
“…In this study, Pramanik et al followed 185 patients with T2DM who received vitamin B, vitamin C, and vitamin E together with antidiabetic medication and 175 patients with T2DM who were treated with only antihyperglycemic drugs for five years. The group with vitamin supplementation had a slower rate of the development of diabetic retinopathy and reduced ROS markers [ 12 ]. It is concluded that vitamin supplementation decreases the development of diabetic microvascular complications via their antioxidant properties.…”
mentioning
confidence: 99%